A scoping review of measurement of violence against women and disability. - Sarah R Meyer; Heidi Stöckl; Cecilia Vorfeld; Kaloyan Kamenov; Claudia García-Moreno (PLoS ONE)
Introduction Existing evidence indicates that prevalence of violence against women with disability is elevated compared to women without disability. We conducted a scoping review with a focus on measurement to assess the forms of measurement and study design utilized to explore the intersection of violence against women with disabilities, and to identify strengths and limitations in current approaches to measuring violence against women with disabilities. This scoping review is designed to inform current debates and discussions regarding how to generate evidence concerning violence against women with disabilities. Methods and results We conducted systematic searches of the following databases: PubMed, PsycINFO, Embase, CINAHL, PILOTS, ERIC, Social Work Abstracts, International Bibliography of the Social Sciences, Social Services Abstracts, ProQuest Criminal Justice, and Dissertations & Theses Global, and conducted structured searches of national statistics and surveys and grey literature available on-line. We identified 174 manuscripts or reports for inclusion. n = 113 manuscripts or reports utilized acts-specific measurement of violence. In terms of measurement of disability, we found that amongst the included manuscripts and reports, n = 75 utilized measures of functioning limitations (n = 20 of these were Washington Group questions), n = 15 utilized a single question approach and n = 67 defined participants in the research as having a disability based on a diagnosis or self-report of a health condition or impairment. Discussion This scoping review provides a comprehensive overview of measurement of violence against women with disabilities and measurement of violence within disability-focused research. We identified several important gaps in the evidence, including lack of sex and disability disaggregation, limited evidence concerning adaptation of data collection methods to ensure accessibility of research activities for women with disabilities, and limited evidence concerning differential relationships between types of disability and violence exposure. This scoping review provides directions for sub-analyses of the included studies and further research to address gaps in evidence.